Erythronecroptosis: an overview of necroptosis or programmed necrosis in red blood cells - Tkachenko, Anton; Havranek, Ondrej (Molecular and cellular biochemistry, 2024)
Necroptosis is considered a programmed necrosis that requires receptor-interacting protein kinase 1 (RIPK1), receptor-interacting protein kinase 3 (RIPK3), and pore-forming mixed lineage kinase domain-like protein (MLKL) to trigger a regulated cell membrane lysis. Membrane rupture in necroptosis has been shown to fuel innate immune response due to release of damage-associated molecular patterns (DAMPs). Recently published studies indicate that mature erythrocytes can undergo necroptosis as well. In this review, we provide an outline of multiple cell death modes occurring in erythrocytes, discuss possible immunological aspects of diverse erythrocyte cell deaths, summarize available evidence related to the ability of erythrocytes to undergo necroptosis, outline key involved molecular mechanisms, and discuss the potential implication of erythrocyte necroptosis in the physiology and pathophysiology. Furthermore, we aim to highlight the interplay between necroptosis and eryptosis signaling in erythrocytes, emphasizing specific characteristics of these pathways distinct from their counterparts in nucleated cells. Thus, our review provides a comprehensive summary of the current knowledge of necroptosis in erythrocytes. To reflect critical differences between necroptosis of nucleated cells and necroptosis of erythrocytes, we suggest a term erythronecroptosis for necroptosis of enucleated cells.
Keywords: Necroptosis; serin-threoninkinasy interagující s receptory; erytrocyty; Erythrocytes; signální transdukce; Eryptosis; eryptóza; proteinkinasy; Protein Kinases; Animals; Necrosis; lidé; Receptor-Interacting Protein Serine-Threonine Kinases; nekroptóza; nekróza; Humans; zvířata; Signal Transduction